Low‐Molecular‐Weight CXCR4 Ligands with Variable Spacers. Issue 1 (19th October 2012) - Narumi, Tetsuo; Aikawa, Haruo; Tanaka, Tomohiro; Hashimoto, Chie; Ohashi, Nami; Nomura, Wataru; Kobayakawa, Takuya; Takano, Hikaru; Hirota, Yuki; Murakami, Tsutomu; Yamamoto, Naoki; Tamamura, Hirokazu
Abstract Low‐molecular‐weight CXCR4 ligands based on known lead compounds including the 14‐mer peptide T140, the cyclic pentapeptide FC131, peptide mimetics, and dipicolylamine‐containing compounds were designed and synthesized. Three types of aromatic spacers, 1, 4‐phenylenedimethanamine, naphthalene‐2, 6‐diyldimethanamine, and [1, 1′‐biphenyl]‐4, 4′‐diyldimethanamine, were used to build four pharmacophore groups. As pharmacophore groups, 2‐pyridylmethyl and 1‐naphthylmethyl are present in all of the compounds, and several aromatic groups and a cationic group from 1‐propylguanidine and 1, 1, 3, 3‐tetramethyl‐2‐propylguanidine were also used. Several compounds showed significant CXCR4 binding affinity, and zinc(II) complexation of bis(pyridin‐2‐ylmethyl)amine moieties resulted in a remarkable increase in CXCR4 binding affinity.